2011
DOI: 10.1002/mnfr.201000641
|View full text |Cite
|
Sign up to set email alerts
|

The role of antioxidant versus pro‐oxidant effects of green tea polyphenols in cancer prevention

Abstract: Consumption of green tea (Camellia sinensis) may provide protection against chronic diseases, including cancer. Green tea polyphenols are believed to be responsible for this cancer preventive effect, and the antioxidant activity of the green tea polyphenols has been implicated as a potential mechanism. This hypothesis has been difficult to study in vivo due to metabolism of these compounds and poor understanding of the redox environment in vivo. Green tea polyphenols can be direct antioxidants by scavenging re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
178
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(184 citation statements)
references
References 98 publications
4
178
0
2
Order By: Relevance
“…EGCG-mediated inhibition of chemokine Agata . Zak, Ilona Pokora production and chemokine interactions with their receptors on white blood cell surface may alter the range and magnitude of the inflammatory response including white blood cell count and pattern (Forester, Lambert, 2011). Our findings showed that 6-week GTE supplementation resulted in a significant increase in the absolute eosinophil count as well as eosinophil percentage in both study groups.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…EGCG-mediated inhibition of chemokine Agata . Zak, Ilona Pokora production and chemokine interactions with their receptors on white blood cell surface may alter the range and magnitude of the inflammatory response including white blood cell count and pattern (Forester, Lambert, 2011). Our findings showed that 6-week GTE supplementation resulted in a significant increase in the absolute eosinophil count as well as eosinophil percentage in both study groups.…”
Section: Discussionmentioning
confidence: 58%
“…Green tea extract and EGCG exert the pro-oxidative effect in subjects with low baseline oxidative stress, whereas green tea poliphenols may be scavenging ROS in subjects with high baseline oxidative stress. According to Forester and Lambert suggestion, with moderate and low concentrations EGCG, low level oxidative stress may be a beneficial cue for the body to initiate induction of protective anti-oxidant systems and host immune responses (Lambert, Elias, 2010), (Forester, Lambert, 2011). Thus under same (exercise, training) conditions with increased oxidative stress, supplementation of green tea polyphenols may attenuated ROS mediated tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary components, like vitamins and polyphenols, also contribute in maintaining intracellular redox homeostasis [26,27]. An increasing numbers of studies have demonstrated that GTPs are strong antioxidant compounds [21,28], nonetheless GTPs are also able to exert pro-oxidant effects. The pro-oxidant/antioxidant behavior of GTPs greatly depend on many experimental conditions, such as final concentration of use, temperature, pH, presence of metal ions, and differences in culture media composition [21,[29][30][31].…”
Section: Effects Of Gtcs On Cellular Redox Homeostasis and Antioxidanmentioning
confidence: 99%
“…Transition metals are able to initiate the catechins auto-oxidation reaction, also promoting the formation of catechins-metal ions complexes. Depending on the experimental model these mechanisms have been correlated both to an antioxidant or a pro-oxidant behavior of GTCs [21,28]. Zinc is required for normal prostate metabolism due to its ability to inhibit aconitase activity determining the excretion of citrate into seminal fluid.…”
Section: Effects Of Gtcs On Intracellular Ros Productionmentioning
confidence: 99%
“…Tea consumption has been reported to have beneficial effects against different types of cancers due to its antioxidants which have the ability to prevent and control cancer development. Many in vivo studies conducted with rodents have shown that tea protects against many types of cancer and at most stages of carcinogenesis [16].Green tea and green tea polyphenols have been shown to have anti-cancer activity in a number of laboratory studies, which could be mediated through antioxidant or pro-oxidant mechanisms [17].Green tea polyphenols such as EGCG inhibit cell viability and induce apoptosis in a number of cancer cell lines such as osteogenic sarcoma [18], lymphoblastoid cells [19], leukemia cells [20], melanoma cells [21], T lymphocytes [22] and larynx carcinoma [23]. EGC can inhibit breast cancer cell viability through induction of apoptosis, yet not in normal breast cells [24].…”
Section: Health Benefits Of Green and Black Tea 41 Cancer Prevenmentioning
confidence: 99%